D’une eau-problème à une eau-ressource : bascule dans nos rapports aux eaux usées traitées - Anne-Laure Collard (Développement Durable et Territoires)
As with all technical infrastructures, treatment and sanitation contribute to shaping society’s relationship with water. Particularly since the 1960s, when there has been growing interest around the world, and more recently in France, in the practice of reusing treated wastewater (wwtr) as a response to scarcity. wwtr is emerging as a new technical response to scarcity, different from more conventional infrastructures (dams, transposition). In France, however, this practice raises the question of how wastewater actually exists. For a long time, this pathogen-charged water was synonymous with a health problem, but now this water is seen as a resource to be valorised, and the challenge is to reintroduce it into a society that has rejected it. Based on an empirical study, this article examines the performative effects of this technical adjustment on the relationship between wastewater and the inhabitants of an area in the Occitanie Region of France faced with a shortage of water. The discourses collected reflect the political project underlying the wwtr, through the idea of virtuous recycling and promising fluidity.